2021
DOI: 10.3390/md19010017
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Microviridin from Cyanobacteria

Abstract: Cyanobacteria are a rich source of secondary metabolites with a vast biotechnological potential. These compounds have intrigued the scientific community due their uniqueness and diversity, which is guaranteed by a rich enzymatic apparatus. The ribosomally synthesized and post-translationally modified peptides (RiPPs) are among the most promising metabolite groups derived from cyanobacteria. They are interested in numerous biological and ecological processes, many of which are entirely unknown. Microviridins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 97 publications
(232 reference statements)
2
56
0
Order By: Relevance
“…To date, most research has focused on the evaluation of environmental conditions that trigger toxin production and its dynamics, which can be essential for understanding of the toxicity and its predicting [ 31 ]. Although the role of environmental factors is not sufficiently understood and the results were widely disputed, many physiological studies demonstrated the influence of light, nutrient availability, temperature, pH and dissolved inorganic carbon (DIC) on enhancing or suppressing the production of different toxic compounds [ 88 , 96 , 97 , 111 , 118 , 119 , 120 , 121 ]. Evidence suggested that generally increased temperatures and light favor the growth of toxin producers and can enhance the toxin production [ 83 , 88 , 122 ], but at times, as for other factors, conflict results.…”
Section: Phycotoxins and Factors That Affect Their Productionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, most research has focused on the evaluation of environmental conditions that trigger toxin production and its dynamics, which can be essential for understanding of the toxicity and its predicting [ 31 ]. Although the role of environmental factors is not sufficiently understood and the results were widely disputed, many physiological studies demonstrated the influence of light, nutrient availability, temperature, pH and dissolved inorganic carbon (DIC) on enhancing or suppressing the production of different toxic compounds [ 88 , 96 , 97 , 111 , 118 , 119 , 120 , 121 ]. Evidence suggested that generally increased temperatures and light favor the growth of toxin producers and can enhance the toxin production [ 83 , 88 , 122 ], but at times, as for other factors, conflict results.…”
Section: Phycotoxins and Factors That Affect Their Productionmentioning
confidence: 99%
“…The hypotheses of physiological aide of toxins in relation with cell signaling were connected with experiments on cultivation conditions for studying the effects regulated by quorum sensing [ 120 ]. Although some contrasting results were reported, the impact of high cell density (HD) cultivation on the production of secondary metabolites in two terrestrial Nostoc strains revealed the importance of cell density and cell-type specific expression [ 103 , 107 ].…”
Section: Phycotoxins and Factors That Affect Their Productionmentioning
confidence: 99%
See 3 more Smart Citations